Epigenetics and Nutrition - Lundstrom, Kenneth (International Journal of Nutrition, 2015)
Epigenetic mechanisms based on DNA methylation, histone modifications and RNA interference have recently showed important association to the development of a wide variety of diseases such as cancer, cardiovascular, metabolic, skin, autoimmune diseases and neurologic disorders. In the context of preventive aspects, the importance of nutrition on epigenetic function has been revealed. Therefore, drastic changes in dietary modifications may contribute to reduced disease risk. For instance, dietary intervention has been showed to affect DNA methylation in Alzheimer’s disease patients. Moreover, maternal high-fat diet can regulate gene expression through promoter histone modifications. Most importantly, RNA interference and particularly micro-RNA mediated regulation of gene expression has been linked to disease development. Remarkably, dietary intake has been demonstrated to significantly affect various miRNAs and their regulation on gene function. In this review, the relationship between epigenetics and disease and development of drugs based on epigenetic targets is presented as well as the influence of dietary intake on epigenetic mechanisms and its effect on disease prevention and therapy will be discussed.
Keywords: Epigenetics; nutrition; DNA methylation; histone modifications; RNA interference; micro-RNA; disease prevention